Fracture Resistance and Microleakage around Direct Restorations in High C-Factor Cavities - Battancs Emese; Sáry Tekla; Molnár Janka; Braunitzer Gábor; Skolnikovics Máté; Schindler Árpád; Szabó Balázs P; Garoushi Sufyan; Fráter Márk (Switzerland, 2022)
The aim of this research was to evaluate the mechanical impact of different direct restorations in terms of fracture resistance, and subsequent fracture pattern, in occlusal high C-factor cavities. Furthermore, the adaptation of different direct restorations in the form of gap formation was also evaluated. Seventy-two intact mandibular molars were collected and randomly distributed into three groups (n = 24). Class I occlusal cavities with standardized dimensions were prepared in all specimens. After adhesive treatment, the cavities were restored with direct restorations utilizing three different materials. Group 1: layered conventional packable resin composite (Filtek Ultimate), Group 2: bulk-fill resin composite (SDR), Group 3: bulk-fill short fibre-reinforced composite (SFRC; everX Posterior) covered with packable composite occlusally. Half of the restored specimens underwent static load-to fracture testing (n = 12/group), while the rest underwent sectioning and staining for microleakage evaluation and gap formation analysis. Fracture patterns were evaluated visually among the mechanically tested specimens. The layered composite restoration (Group 1) showed significantly lower fracture resistance compared to the bulk fill groups (Group 2, p = 0.005, Group 3, p = 0.008), while there was no difference in fracture resistance between the other groups. In terms of gap formation values, the layered composite restoration (Group 1) produced significantly higher gap formation compared to the bulk-fill groups (Group 2, p = 0.000, Group 3, p = 0.000). Regarding the fracture pattern, SFRC (Group 3) produced the highest number, while SDR (Group 2) produced the lowest number of repairable fractures. The use of bulk-fill resin composite (fibre or non-fibre-reinforced) for occlusal direct restorations in high C-factor cavities showed promising achievements regarding both fracture resistance and microleakage. Furthermore, the use of short fibre-reinforced bulk-fill composite can also improve the fracture pattern of the restoration-tooth unit. Bulk-fill materials provide a simple and effective solution for restoring and reinforcing high C-factor occlusal cavities.